Estudo das propriedades de pastilhas e fios supercondutores do sistema BSCCO dopados com compostos nanoparticulados de cálcio - Nogueira, Natacha Andréia [UNESP] (Universidade Estadual Paulista (Unesp), 2014)
The present work was designed to test the addition of a little proportion (1 wt,%) of two calcium compounds, calcium silicate and calcium e o zirconate, in the preparation of Bi:2212 silver sheathed wires, which were successfully tested in processing of melt-textured pellets and were observed in the microstructure in function of the use calcium compound. Three heat treatments with nearby values to the maximum temperatures, but slightly different were applied to the wires in O2/Ar atmosphere using the partial-melting method. Analysis of X-ray diffraction performed in the removed powder from the ceramic core of treated wires showed the predominance of the Bi:2212 phase, despite of the presence of a multiphasic character for the samples. Thermogravimetry and differental thermal analysis were performed in the ceramic powders used to prepare the wires. Observations of longitudinal and cross sections of the wires performed in a scanning electron microplate presence of the superconductiong phase accompanied by more or less segregation of phase rich in copper. The treatments with higher maximum temperatures are more effective to improving the superconducting properties that were evaluated that were evaluated using tranport and megnetic measurements. The critical temperatures were higher that 100K. The critical current densities obtained by transport measurments ranged from 3.44/cm2 (reference wire treated up 880ºC) to 38.8A/cm2 (wire with addition of CaSiO3) treated up 883ºC), this higher value is related to microstructure with addition of CaSiO3 treated up 883ºC), this higher value is related to microstructure with a higher proportion of microplates and smaller proportion of segregated phase. The critical current density determined by magnetization produced much higher values because they are based on a critical model, the Bean Model. The same wire observed like the better in electrical measurements also also showed higher values when...

O presente trabalho visou testar a adição de uma pequena proporção (1% em peso) de dois compostos de cálcio, o silicato de cálcio e o zirconato de cálcio, na preparação de fios de Bi:2212 revestidos com prata, os quais foram testados com sucesso anteriormente em processamento de pastilhas e foram observadas grandes alterações na microestrutura em função do composto de cálcio utilizado. Três tratamentos térmicos com temperaturas máximas próximas, mas ligeiramente diferentes, foram aplicados aos fios em atmosfera de O2/Ar usando o método de fusão parcial. Análises de difração de raio-X realizadas nos pós removidos do núcleo cerâmico dos fios mostraram a predominância da fase Bi:2212, apesar de apresentarem um caráter multifásico. Análise térmica diferencial e termogravimétrica foram feitas nos pós cerâmicos utilizados na preparação dos fios. Observação das seções transversais e longitudinais dos fios realizadas em microscópio eletrônico de varredura indicam a presença de feixes de microplacas da fase supercondutora acompanhadas de maior ou menor segregação de fase rica em cobre. Os tratamentos com temperaturas máximas mais elevadas se mostram mais eficazes para a melhoria das propriedades supercondutoras que foram avaliadas utilizando-se medidas de transporte e medidas magnéticas. As temperaturas críticas foram superiores a 100k. As densidades de corrente crítica obtidas por medidas de transporte variaram de 3,4A/cm2 (fio de referência tratado até 880ºC) a 38,8A/cm2 (fio com adição de CaSiO3 tratado até 883ºC), este valor mais elevado está relacionado a microestrutura com maior proporção de microplacas e menor proporção de fase segregada. A densidade de corrente crítica determinada por magnetização produziram valores muito mais altos por serem baseados em um modelo, o Modelo de Bean. O mesmo fio observado como melhor nas medidas elétricas também apresentou valores superiores quando...
Keywords: Supercondutores; Fios; Raios X - Difração; Microestrutura; Superconductors